Isolation of dematiaceous pathogenic fungi from a feed and seed warehouse. - Espinel-Ingroff, A (1982)
In an epidemiological study, nine isolates of dematiaceous fungi were recovered from the interior of a local feed and seed warehouse. Sample sites include brick walls and floors. Air samples also were included. Samples were collected in saline and plated on Mycobiotic and Sabouraud agar. The nine dematiaceous fungi recovered from these samples were identified with microscopic morphology, thermotolerance, biochemical reactions, and animal virulence test. Four isolates were identified as nonpathogens on the basis of positive gelatin tests. The identified pathogens included Fonsecaea pedrosoi, Cladosporium bantianum (C trichoides), Wangiella dermatitidis (Dixon et al., Mycopathologia 70:153-161, 1980), and Exophiala jeanselmei. These five organisms were injected into NCI/ALB mice. Only the isolate of C. bantianum was neurotropic, as demonstrated histopathologically and by the recovery of the organism from brain tissue. None of the remaining four isolates were seen or cultured from any of the mouse tissues analyzed. The recovery of pathogenic dematiaceous fungi from environmental sites is not uncommon. However, this study is noteworthy in that it represents only the second reported isolation of C. bantianum and the first isolation of F. pedrosoi from the environment in North America and suggests that these fungi may be more ubiquitous in this region that previously believed.